A Revisit of Direct and Diffuse Solar Radiation in China Based on Homogeneous Surface Observations: Climatology, Trends, and Their Probable Causes. Issue 9 (11th May 2020) - Wang, Yawen; Yang, Su; Sanchez‐Lorenzo, Arturo; Yuan, Wenping; Wild, Martin
Abstract: Increasing energy and food demands require an understanding of not only the availability and variability of total solar radiation ( R ) but also its partitioning into direct ( R d ) and diffuse ( R f ) components, which are key elements for solar power generation and plant photosynthesis, respectively. Potential inhomogeneities in surface solar radiation observations, however, add uncertainties to the published patterns and trends of R d and R f over China. To exclude inhomogeneous time series and outliers, a data quality control process has been applied to the surface observations of R d and R f . The homogeneous data show that, in response to the global dimming and brightening phenomena in R, decadal changes can also be observed in the R d and R f trends over China with the actual transition occurring in the mid‐2000s. Since the 1960s, R d dimming has mainly distributed over eastern China with intensive anthropogenic activities, with recoveries especially from 2008 onward over regions with high R d energy potential. R f, on the other hand, had further enhanced since the 1960s especially over the high R f proportion areas but has decreased in the recent decade over the northern region. The summer season shows the most significant decadal trends in R d and R f . Under clear‐sky conditions, that is, ruling out cloud effects, the transitions in R d and R f trends become more remarkable, pointing to atmospheric aerosols as the main driving force. In addition, dramatic R d and R f variations are observed in the subsequent years after large volcanic eruptions. The varying R d and R f proportions are in line with recent governmental control on SO2 emissions over China. Key Points: Homogeneous observations show a recent transition to brightening in direct radiation and to dimming in diffuse radiation over China since 2008 Clear‐sky trends suggest an impact of volcanic eruption on the dramatic changes in solar radiation over China during the early 1990s Governmental control on pollutant emissions may have contributed to the variations of direct and diffuse radiation proportions over China